SOSIALISASI PERPAJAKAN PELAKU UMKM DI KELURAHAN GUNUNG SAMARINDA - Matyani, Matyani; Sarah Octavia, Gusti; Angellika, Maria; sofyaun, Ashari; Lestari, Winda (Jurnal Abdi Masyarakat Ilmu Ekonomi (JAMIE), 2025)
One of the problems faced by Micro, Small and Medium Enterprises (UMKM) in Mt. Samarinda Village, North Balikpapan District, is the lack of understanding of tax obligations. Many UMKM actors are not aware of the importance of paying taxes and the benefits that can be obtained from tax compliance, such as access to various government facilities and programs. As an effort to increase this awareness, the UMKM Tax Socialization program was carried out, which aims to 1) Increase the understanding of UMKM actors regarding tax obligations and tax administration procedures; 2) Assisting business actors in calculating, reporting, and paying taxes in accordance with applicable regulations; 3) Encourage tax compliance so that UMKM can develop more professionally and contribute to regional development. The results of this socialization program show that UMKM actors better understand the importance of paying taxes and how to implement them. In addition, they also get solutions to tax problems that are often faced in running their businesses